PENGGUNAAN BAHASA ISYARAT INDONESIA (BISINDO) DALAM INTERAKSI SOSIAL (STUDI PADA KOMUNITAS BAMBU TULI BEKASI) - Amaldin Fajar Hanantyo (2020)
This research is motivated by the struggle of deaf people to introduce sign language as a way of their communication. There are two types of sign languages in Indonesia namely Bisindo (Indonesian Sign Language) and SIBI (Indonesian Sign Language System). Until now the government still stipulates SIBI as a language curriculum in each Special School (SLB) in Indonesia and it is rejected by deaf people because Bisindo is considered to be more representative of their existence and easier to use. Their struggle against Bisindo was accompanied by the formation of deaf communities such as the Deaf Bamboo Community in Bekasi. The formulation of the problem in this research is how the use of symbols or symbols in the use of Bisindo in the Bekasi Tuli Bamboo Community with the aim to find out how the translation and meaning of the Bisindo movement and to understand the socialization of Bisindo. The research method used is qualitative by collecting data through observation, interviews, and documentation. The theory used in this research is the symbolic interaction of George Herbert Mead. The results showed that Bisindo was championed by the Bamboo Deaf Community in Bekasi by carrying out various activities, the use of the Bisindo symbol, and differences in the ability of deaf interactions. This research shows the symbolic interaction of Bisindo in social interaction in the Deaf Bamboo Community in Bekasi. Symbolic interactions are related to symbols and interactions. The symbolic meaning of Bisindo further clarifies something to be easier and more concise and the symbol is used instead of words in languages whose names are more specific and have been agreed upon in advance. Not all deaf people have the same intelligence. Differences in intelligence affect social interaction, the better the level of intelligence the better the achievement and experience gained. Keywords: Sign Language, Bisindo, Social Interaction, Symbolic Interaction, Deaf Community